2021
DOI: 10.5937/psistra24-32799
|View full text |Cite
|
Sign up to set email alerts
|

Trends in primary school teachers' experience over the first year of the COVID-19 pandemic in Serbia: A narrative analysis

Abstract: The purpose of the study is to explore the experiences shared by primary school teachers in three waves of data collection. Teachers' narratives about their experiences of schooling during the COVID-19 pandemic were elicited online. In three instances, a total of 116 participants were prompted to narrate in story and letter genres, providing 233 narratives. We conducted the values analysis and additionally analysed data statistically in order to compare the values teachers expressed at three key turning points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It is highly recommended to provide better communication facilites to distance learners through digital support by student support services (Anjum & Iqbal, 2020). Finally, building teachers' competencies and skills for all aspects of distance education, starting from the initial education of teachers, is essential (Mićić et al, 2021).…”
Section: Technical Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…It is highly recommended to provide better communication facilites to distance learners through digital support by student support services (Anjum & Iqbal, 2020). Finally, building teachers' competencies and skills for all aspects of distance education, starting from the initial education of teachers, is essential (Mićić et al, 2021).…”
Section: Technical Barriersmentioning
confidence: 99%
“…In parallel, Mićić et al (2021) put the spotlight on the change and dynamic shift in the way teachers have positioned themselves across the COVID-19 pandemic time in Serbia:…”
Section: Psychological Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study by Sokal et al (2020) demonstrated that while teachers in Canada had positive attitudes towards COVID-induced changes in education in the early stage of the pandemic, in the following months such attitudes became less optimistic. Mićić et al (2021) showed that in the initial stages of the COVID-19 pandemic, teachers' concerns in Serbia were mostly related to immediate health dangers, frustration, and pressure, while in the later stages concerns related to the quality of education became predominant. This intensive dynamic of the educational landscape during the pandemic was recognized as one of the key features of ERE.…”
Section: Emergency Remote Educationmentioning
confidence: 99%